Writing Modernity from the East: Secularism, Tradition and Modernism in the Works of Yitzhaq Shami - Dotan, Keren (MiKAN, 2017)
This essay aims to challenge the way Hebrew literary criticism reads Shami's works and its dichotomous conception of modernism and Mizrahiness. Through a close reading of the stories "The Barren Wife," "Ransom," "Flight," "Hamamah: A Tale of the Arabian Desert," "Father and Daughters" and "The Vengeance of the Fathers, "this essay seeks to trace the ways in which Shami challenges the progressive timeframe that underlies the European-Mizrahi opposition as well as Zionist perceptions of secularism and tradition.